2020
DOI: 10.1038/s41598-020-65562-4
|View full text |Cite
|
Sign up to set email alerts
|

Temperature elevation in tissue detected in vivo based on statistical analysis of ultrasonic scattered echoes

Abstract: It is demanded to monitor temperature in tissue during oncological hyperthermia therapy. In the present study, we non-invasively measured the temperature elevation inside the abdominal cavity and tumour tissue of a living rat induced by capacitive-coupled radiofrequency heating. In the analysis of ultrasound scattered echoes, the Nakagami shape parameter m in each region of interest was estimated at each temperature. The Nakagami shape parameter m has temperature dependence; hence, the temperature increase ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…6). Our group previously reported similar results, indicating that the mean absolute values of the percentage changes in m values rise precipitously in regions with small temperature changes (Takeuchi et al 2018(Takeuchi et al , 2020. In this study, the upturn in the variation in the mean value of a mod is considered to reflect the slight temperature increase inside the tumor tissue immediately after the RF current was first applied.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…6). Our group previously reported similar results, indicating that the mean absolute values of the percentage changes in m values rise precipitously in regions with small temperature changes (Takeuchi et al 2018(Takeuchi et al , 2020. In this study, the upturn in the variation in the mean value of a mod is considered to reflect the slight temperature increase inside the tumor tissue immediately after the RF current was first applied.…”
Section: Discussionsupporting
confidence: 60%
“…In our previous study, we reported that the spatial gradient in the temperature distribution inside a locally heated soft tissue specimen could be clearly visualized on 2-D a mod maps (Takeuchi et al 2019). Recently, we reported the results of our in vivo studies using SpragueÀDawley rats (Takeuchi et al 2020). In these in vivo studies, the temperature elevation inside the abdominal cavity and tumor tissue of a living rat induced with RF current heating was detected on hot-scale images, indicating the absolute values of the percentage changes in m values, a mod .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Our previous studies have indicated that the absolute value of the ratio change in the logarithmic NA parameter visualizes the temperature change inside tissue‐mimicking phantoms and ex vivo and in vivo biological soft tissues 21–23 . Another previous study has also demonstrated that the temperature change is related to variations in the ultrasonic envelope statistical properties 24 .…”
Section: Introductionmentioning
confidence: 96%